Analysis of Human Resources Performance in Public Banks in Banten Province Using SWOT Analysis and Balance Scorecard Methods - Sarwani, Sarwani (Universitas Pamulang, 2023)
Research that focuses on the analysis of human resource (HR) performance at Rural Banks (BPR) in Banten Province, using the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) and Balance Scorecard. This research was conducted with the aim of assessing HR performance in the context of a bank and identifying the factors that influence this performance. The research methodology uses a qualitative descriptive research method, with data collection through interviews, observation, and documentation. The results of data analysis were processed using Miles and Huberman's steps, including data reduction, data presentation, and drawing conclusions. In terms of HR performance analysis, this study combines the SWOT analysis and Balance Scorecard approaches. From the analysis results, This study identified the internal strengths and weaknesses of Rural Banks in the Province of Banten, as well as external factors of opportunities and threats that affect the company's performance. These factors are evaluated by giving weights and ratings, which are then used to formulate appropriate strategic choices. The final result of the SWOT matrix analysis shows strategic issues that need to be considered by Rural Banks in Banten Province. Several strategic issues include employee discipline, customer service, product development, Bank Indonesia policies, employee growth in accordance with policies, provision of quality products, and improvement of service facilities such as ATMs. Overall,